Effectiveness of a local strain of Bacillus thuringiensis in the management of castor semilooper, Achaea jaizata on castor (Ricizus communis) - DEVI, P S VIMLA; SUDHAKAR, R (The Indian Journal of Agricultural Sciences, 2011)
Formulation of a local strain of Bacillus thuringiensis ( B r ) var. kttrstaki, viz DOR Bt- I . obtained through multiplication on a wheat bran based solid substrate was tested against castor semilooper field. Field trials showed that a single spray of the formulation at the dose of 1.5 g / litre gave ef’kctive control of castor semi looper till 30 days atier spraying. Incedence of the larval parasitoid (micropilitis maculipennis was observed only in Bt sprayed fields. Continuous egg laying and high larval incidence necessitated five sprays in tlie cluinalphos sprayed fields at 6-7 days intervals. Iticremcntal cost:benefit ratlo for thc Br spray was found to be 3.85 while it was 1.62 for quinalphos.